Mini review on the ethical use of AI bots in academic writing / Siti Syairah Mohd Mutalip ... [et al.] - Mohd Mutalip, Siti Syairah; Hussin, Siti Nooraishah; Mohd Yusoff, Rosmadi; Mohd Rocky, Nik Ateerah Rasheeda; Mohd Nawi, Mohd Nasrom; Syed Hussain, Sharifah Salmah; John, Kwong Siew Shia (UiTM Press, 2024)
Academic writing is a specialised form of written communication that prioritizes accuracy and innovation to effectively convey knowledge. Internet bots, such as Grammarly, Quillbot, TextCortex, and ChatGPT, are commonly used to improve academic writing, particularly essays. However, AI bot-generated text has become a concern to educational institutions with academic integrity, as fabricated abstracts have been accepted through peer review processes. AI bots can generate texts, based on a given topic or keyword, leading to plagiarism accusations and misrepresentations of research findings. Researchers should always verify the accuracy and use of correct technical terms for their research write-up. Additionally, relying too heavily on AI-generated texts may result in a lack of creativity and originality, which is important in scientific writing and young scientist grooming. To address these ethical issues, OpenAI has developed a free tool called AI text Classifier13 to distinguish between AI-written and human-written texts. However, this tool has been described as an ‘imperfect tool’ by OpenAI, warning that it should not be used as a primary decision-making tool. Academic and research institutions must accept the revolution of generative AI tools in academic writing, as it is not sustainable to ban or deny it. AI tools can be efficient and time-saving for both lecturers and students, but acknowledging AI tools should be included in academic integrity policies. Additionally, institutions with current assessment methods based on written essays may need to change from accessing finished essays to assessing critical thinking through additional oral examinations.